Application of Expert Decision Systems for Optimal Fiber Selection for Green Building Design Components - Balo, Figen; Sua, Lutfu S. (Emerald Group Publishing Ltd., 2023)
Composites based on fiber are commonly used in high-performance building materials. The composites mostly use petrochemically derived fibers like polyester and e-glass, due to their advantageous material features like high stiffness and strength. All the same, these fibers also have important shortcomings related to energy consumption, recyclability, initial processing expense, resulting health hazards, and sustainability. Increasing environmental awareness and new sustainable building technologies are driving the research, development, and usage of “green” building materials, especially the development of biomaterials. In this chapter, the natural fiber evaluation approach is applied, which covers a diverse set of criteria. Consequently, the comparative assessment of diverse natural fiber types is applied through the use of an expert decision system approach. The best performing fiber choice is made by comparatively evaluating the materials related to green building. The proposed fiber can be used and applied by green building material manufacturing companies in various countries or locations as a reference when selecting the fiber with the best performance. © 2023 Figen Balo and Lutfu S. Sua.
Keywords: AHP; biomass; green building; Natural fiber; renewable material; synthetic fiber